The Role of Adolescent Health Cadres on Cervical Cancer Prevention for Women of Reproductive Age - Rodiyatun Rodiyatun; Suryaningsih Suryaningsih; Sutio Rahardjo; Siti Anisak (Alliance oh Health Activists (AloHA), 2019)
Poverty and low education of women is a determinant that causes women to be powerless to avoid risk factors and to prevent cervical cancer. Basically many health promotion and education efforts on cervical cancer have been carried out by implementing various health promotion strategies and methods. The purpose of this study is to analyze the influence of the role of adolescent health cadres on cervical cancer prevention behavior in women of reproductive age. Type of this research was quasy experiment with pre and post test control group design. The population was female adolescents, 11th and 12th grade students of MAN Bangkalan (high school) and their mothers, 40 samples in the observation group and 40 in the control group. The sampling technique used was simple random sampling. The independent variables was the role of adolescent health cadres, and the dependent variables were cognition, self-efficacy, commitment, prevention. Data were collected using questionnaire, then analyzed using Mann-Whitney Test and Wilcoxon test. The test results showed that the role of adolescent health cadres influenced the behaviour of prevention and early detection of cervical cancer in women of reproductive age, meaning that the development of the role of adolescent health cadres as health information providers can create a condusive atmosphere for changes in health behaviour in their families. Keywords: cervical cancer; the role of adolescents; prevention